2006
DOI: 10.1186/1749-8090-1-8
|View full text |Cite
|
Sign up to set email alerts
|

Secondary left ventricular injury with haemopericardium caused by a rib fracture after blunt chest trauma

Abstract: Trauma is the third most common cause of death in the West. In the US, approximately 90,000 deaths annually are traumatic in nature and over 75% of casualties from blunt trauma are due to chest injuries. Cardiac injuries from rib fractures following blunt trauma are extremely rare. We report the unusual case of a patient who fell from a height and presented with haemopericardium and haemothorax as a result of left ventricular and lingular lacerations and was sucessfully operated upon. Case reportA 55 year old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…The initial chest X-ray (Figure 1) is also of particular interest as it shows an essentially normal anteroposterior film with perhaps a globular or enlarged cardiac silhouette, a feature noted more clearly in other reports [16]. However, the difficultly in determining acute cardiac sizing when only a single anteroposterior film is used and how the increased sensitivity of echocardiography immediately clinched the diagnosis must again be acknowledged.…”
Section: Case Presentationmentioning
confidence: 80%
“…The initial chest X-ray (Figure 1) is also of particular interest as it shows an essentially normal anteroposterior film with perhaps a globular or enlarged cardiac silhouette, a feature noted more clearly in other reports [16]. However, the difficultly in determining acute cardiac sizing when only a single anteroposterior film is used and how the increased sensitivity of echocardiography immediately clinched the diagnosis must again be acknowledged.…”
Section: Case Presentationmentioning
confidence: 80%
“…It is understandable, therefore, that survival after blunt cardiac rupture is extremely low. In fact, a literature review between 1957 and 2017 revealed that there were only 15 reports of patients surviving after sustaining blunt cardiac rupture in the past 60 years [ [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] ]. To the best of our knowledge, this is now the 16th survivor of blunt cardiac rupture.…”
Section: Discussionmentioning
confidence: 99%
“…Our case was interesting because, this injury was due to a low velocity injury - an uncommon injury mechanism that has only been reported three times in the medical literature [ [20] , [21] , [22] ]. In 1968, Suszoko et al reported a similar injury after a man fell over onto a chair [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Penetrating heart injuries should be considered in cases where there is hemopneumopericardium noted in the thorax CT, injuries present in the front side of the chest wall, especially parasternal rib detachments, flail chest, sternal fracture, massive hemothorax and in patients who are unresponsive to the fluid-blood replacement therapy [5][6][7].…”
Section: Discussionmentioning
confidence: 99%